Analysis of aromatic acids by nonaqueous capillary electrophoresis with ionic‐liquid electrolytes. Issue 23 (13th October 2014) - Lu, Yuanqi; Wang, Dunqing; Kong, Chunyan; Zhong, Hao; Breadmore, Michael C.
<x xml:space="preserve">Abstract</x> The separation of six kinds of aromatic acids by CZE with 1‐ethyl‐3‐methylimidazolium chloride (EMIMCl) and 1‐ethyl‐3‐methylimidazolium hydrogen sulfate (EMIMHSO4), two kinds of ionic liquids (ILs) as background electrolytes, and acetonitrile as solvent were investigated. The six kinds of aromatic acids can be separated under positive voltage with low IL concentration with either of the two ILs and separation with EMIMHSO4 is better in consideration of peak shapes and separation efficiency. But the migration order is different when the IL is different. Under negative voltage with high IL concentration, the six analytes can be separated with EMIMCl as background electrolytes and the migration order of the analytes is opposite to those with low concentration of EMIMCl as background electrolyte. The separations are based on the combination effects of heteroconjugation between the anions and cations in the ILs and the analytes, of which the heteroconjugation between the anions in the ILs and the analytes plays a dominant role. The heteroconjugation between the anions of the ILs and analytes is proton sensitive and only a very small amount of proticsolvents added into the electrolyte solution can harm the separation. When EMIMCl concentration is high, the heteroconjugation between the IL anions and the proton in the analytes make the effective mobility of the analytes much higher than the EOF and their migration direction reversed. Finally, the six aromatic acids in water samples were analyzed by nonaqueous CE with low concentration of EMIMHSO4 as background electrolytes with satisfactory results.